Chromatin remodeler Ep400 ensures oligodendrocyte survival and is required for myelination in the vertebrate central nervous system - Elsesser, Olga; Fröb, Franziska; Küspert, Melanie; Tamm, Ernst R.; Fujii, Toshihiro; Fukunaga, Rikiro; Wegner, Michael (Nucleic Acids Research, 2019)
Differentiating oligodendrocytes generate myelin to ensure rapid saltatory conduction in the vertebrate central nervous system. Although oligodendroglial differentiation and myelination are accompanied by dramatic chromatin reorganizations, previously studied chromatin remodelers had only limited direct effects on the process. To study the functional significance of chromatin changes for myelination and identify relevant remodelers, we deleted Ep400, the central ATP-hydrolyzing subunit of the TIP60/EP400 complex, at defined times of mouse oligodendrocyte development. Whereas Ep400-deficient oligodendrocyte precursors develop normally, terminal differentiation and myelination are dramatically impaired. Mechanistically, Ep400 interacts with transcription factor Sox10, binds to regulatory regions of the Myrf gene and is required to induce this central transcriptional regulator of the myelination program. In addition to reduced and aberrant myelin formation, oligodendrocytes exhibit increased DNA damage and apoptosis so that numbers never reach wildtype levels during the short lifespan of Ep400-deficient mice. Ep400 deletion in already mature oligodendrocytes remains phenotypically inapparent arguing that Ep400 is dispensable for myelin maintenance. Given its essential function in myelin formation, modulation of Ep400 activity may be beneficial in conditions such as multiple sclerosis where this process is compromised.
CRIS-Team Scopus Importer:2019-07-30

Influence of chromatin remodeler Ep400 on oligodendroglial development - Elsesser, Olga; Wegner, Michael (GLIA, 2019)
CRIS-Team WoS Importer:2020-01-10

Myrf guides target gene selection of transcription factor Sox10 during oligodendroglial development - Aprato, Jessica; Sock, Elisabeth; Weider, Matthias; Elsesser, Olga; Fröb, Franziska; Wegner, Michael (Nucleic Acids Research, 2020)
Oligodendrocytes generate myelin in the vertebrate central nervous system and thus ensure rapid propagation of neuronal activity. Their development is controlled by a network of transcription factors that function as determinants of cell identity or as temporally restricted stage-specific regulators. The continuously expressed Sox10 and Myrf, a factor induced during late development, are particularly important for terminal differentiation. How these factors function together mechanistically and influence each other, is not well understood. Here we show that Myrf not only cooperates with Sox10 during the induction of genes required for differentiation and myelin formation. Myrf also inhibits the activity of Sox10 on genes that are essential during earlier phases of oligodendroglial development. By characterization of the exact DNA-binding requirements of Myrf, we furthermore show that cooperative activation is a consequence of joint binding of Sox10 and Myrf to the same regulatory regions. In contrast, inhibition of Sox10-dependent gene activation occurs on genes that lack Myrf binding sites and likely involves physical interaction between Myrf and Sox10 followed by sequestration. These two opposite activities allow Myrf to redirect Sox10 from genes that it activates in oligodendrocyte precursor cells to genes that need to be induced during terminal differentiation.
CRIS-Team WoS Importer:2020-03-10

SoxD transcription factor deficiency in Schwann cells delays myelination in the developing peripheral nervous system - Ittner, Ella; Hartwig, Anna; Elsesser, Olga; Wüst, Hannah; Fröb, Franziska; Wedel, Miriam; Schimmel, Margit; Tamm, Ernst R.; Wegner, Michael; Sock, Elisabeth (Scientific Reports, 2021)
The three SoxD proteins, Sox5, Sox6 and Sox13, represent closely related transcription factors with important roles during development. In the developing nervous system, SoxD proteins have so far been primarily studied in oligodendroglial cells and in interneurons of brain and spinal cord. In oligodendroglial cells, Sox5 and Sox6 jointly maintain the precursor state, interfere with terminal differentiation, and thereby ensure the proper timing of myelination in the central nervous system. Here we studied the role of SoxD proteins in Schwann cells, the functional counterpart of oligodendrocytes in the peripheral nervous system. We show that Schwann cells express Sox5 and Sox13 but not Sox6. Expression was transient and ceased with the onset of terminal differentiation. In mice with early Schwann cell-specific deletion of both Sox5 and Sox13, embryonic Schwann cell development was not substantially affected and progressed normally into the promyelinating stage. However, there was a mild and transient delay in the myelination of the peripheral nervous system of these mice. We therefore conclude that SoxD proteins—in stark contrast to their action in oligodendrocytes—promote differentiation and myelination in Schwann cells.
CRIS-Team Scopus Importer:2021-07-16

Transcription factor Tcf4 is the preferred heterodimerization partner for Olig2 in oligodendrocytes and required for differentiation - Wedel, Miriam; Fröb, Franziska; Elsesser, Olga; Wittmann, Marie-Theres; Lie, Dieter Chichung; Reis, André; Wegner, Michael (Nucleic Acids Research, 2020)
Development of oligodendrocytes and myelin formation in the vertebrate central nervous system is under control of several basic helix-loop-helix transcription factors such as Olig2, Ascl1, Hes5 and the Id proteins. The class I basic helix-loop-helix proteins Tcf3, Tcf4 and Tcf12 represent potential heterodimerization partners and functional modulators for all, but have not been investigated in oligodendrocytes so far. Using mouse mutants, organotypic slice and primary cell cultures we here show that Tcf4 is required in a cell-autonomous manner for proper terminal differentiation and myelination in vivo and ex vivo. Partial compensation is provided by the paralogous Tcf3, but not Tcf12. On the mechanistic level Tcf4 was identified as the preferred heterodimerization partner of the central regulator of oligodendrocyte development Olig2. Both genetic studies in the mouse as well as functional studies on enhancer regions of myelin genes confirmed the relevance of this physical interaction for oligodendrocyte differentiation. Considering that alterations in TCF4 are associated with syndromic and non-syndromic forms of intellectual disability, schizophrenia and autism in humans, our findings point to the possibility of an oligodendroglial contribution to these disorders.
CRIS-Team Scopus Importer:2020-05-29